INDIVIDUAL ORAL HYGIENE QUALITY INFLUENCE ON THE SEVERITY OF POST-RADIATION MUCOSITIS IN PATIENTS WITH SQUAMOUS CELL CARCINOMA OF THE OROPHARYNGEAL REGION - A. M. Avanesov; E. N. Gvozdikova; T. V. Tarasova; D. A. Khaydar; A. A. Vinogradova; I. A. Zakharkin (Южно-Российский онкологический журнал, 2020)
Purpose of the study. Assessment of the quality of individual oral hygiene in patients with squamous cell oropharyngeal cancer before and after radiation therapy.Materials and methods. Examined 76 patients with squamous cell carcinoma of the oropharyngeal region. For all patients, before and after radiation therapy, evaluated the hygienic state of the oral cavity using indices: index of individual hygiene (Green V.), Silness‑Loe index (GI), index of prevalence of periodontal diseases (CPITN).Results. The number of males was higher than that of females: 52 (68.4%) versus 24 (31.6%). Before radiotherapy, 52 (68.4%) patients had gingivitis, 66 (86.8%) had periodontitis, 43 (56.5%) had metal crowns, and 57 (76%) had destroyed teeth. All patients (100%) had oral mucositis after radiation therapy. We found a significant negative trend: the Green V. index changed by 29.2%, CPITN indicators‑by 38%, GI — by 31.2% (p<0.05). There was also a direct dependence of the severity of oral mucositis on the total dose of radiation. Thus, patients with squamous cell carcinoma of the oropharyngeal region develop severe oral mucositis with a total radiation dose of 30 Gy and above. The probability of occurrence of oral mucositis of 4 severity is possible in 2/3 cases with a total radiation dose of 40 Gy or higher.Conclusion. The severity of oral mucositis depends on both the total radiation dose and the initial dental status of the patient. Therefore, quality control of individual oral hygiene and periodontal support for patients with oral malignancies should be carried out throughout the patient's treatment.